2020
DOI: 10.3389/fimmu.2020.01382
|View full text |Cite
|
Sign up to set email alerts
|

Planned Yellow Fever Primary Vaccination Is Safe and Immunogenic in Patients With Autoimmune Diseases: A Prospective Non-interventional Study

Abstract: Yellow Fever (YF) vaccination is suggested to induce a large number of adverse events (AE) and suboptimal responses in patients with autoimmune diseases (AID); however, there have been no studies on 17DD-YF primary vaccination performance in patients with AID. This prospective non-interventional study conducted between March and July, 2017 assessed the safety and immunogenicity of planned 17DD-YF primary vaccination in patients with AID. Adult patients with AID (both sexes) were enrolled, along with healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
2
15
0
3
Order By: Relevance
“…The viremia peak was 5-6 days after vaccination in all groups but was lower in patients with AID. 97 Overall, these results highlight the importance of evaluating the immunogenicity of the YF-17D vaccine in specific populations and how the prior immune status influences the immune response to YF-17D vaccination. In addition, these studies pinpoint to important immune parameters at baseline or linked to immune status that interfere or hinder with the induction of optimal immune responses.…”
Section: Immunocompromised and Autoimmune Disease Patientsmentioning
confidence: 81%
“…The viremia peak was 5-6 days after vaccination in all groups but was lower in patients with AID. 97 Overall, these results highlight the importance of evaluating the immunogenicity of the YF-17D vaccine in specific populations and how the prior immune status influences the immune response to YF-17D vaccination. In addition, these studies pinpoint to important immune parameters at baseline or linked to immune status that interfere or hinder with the induction of optimal immune responses.…”
Section: Immunocompromised and Autoimmune Disease Patientsmentioning
confidence: 81%
“…The 17DD-YF vaccine induces a safe and effective protective immunity in healthy vaccinees leading to high levels of protection in healthy adults (95–98%) resultant of robust humoral and cellular immunity 7 , 15 19 . Recent evidences have shown that planned primary 17DD-YF vaccination is safe and immunogenic but lower seropositivity rate is overall observed in AID patients upon planned 17DD-YF primary vaccination 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this guideline, our group has previously developed a prospective non-interventional study to assess the safety and immunogenicity of planned 17DD-YF primary vaccination in AID patients 14 . Consistent seroconversion rates (78%) were observed in AID patients, supporting the safety and immunogenicity of planned 17DD-YF primary vaccination for AID patients.…”
Section: Introductionmentioning
confidence: 99%
“… 50 YF vaccination of patients with low-active autoimmune diseases was safe after the withdrawal of immunomodulating therapy, but it led to a lower seropositivity rate (78% versus 96%) at day 28 after vaccination. 51 …”
Section: Discussionmentioning
confidence: 99%